Análise do gene loricrina para avaliação da suspeita de queratodermia loricrina em indivíduos de uma família de Minas Gerais - Bruno Diniz Sander Morais (2012)
The mammals epidermis is constituted of a stratified epithelium formed by a regulated process of keratinocytes differentiation that results in the formation of the mature epidermis. The outermost layer of this tissue, known as stratum corneum, has an important waterproof function and is made up of dead and enucleated keratinocytes named korneocytes. The korneocytes contain juxtaposed keratin filaments, which are linked to the cornified cell envelope. This structure contributes to the protective function of the epidermis and is composed of an external lipid bilayer and an internal protein layer, this one constituted of several kinds of proteins, including loricrin. Loricrin is a basic highly insoluble and glycine-, serine-, cysteine-rich protein. It has a key structure role in cornified cell envelopes function and is responsible for 70% to 85% of its total mass. The gene that encodes this protein is located in 1q21.3 and has two exons. Only the second one is protein coding. Dominant inherited single nucleotide insertions have been reported in the second exon and underlie distinct skin abnormalities, caused by the synthesis of aberrant proteins in which the c-terminal amino acid sequences are replaced by missense amino acids. There isnt a genotype-phenotype correlation in the reported cases. The observable phenotypes are diffuse palmoplantar hyperkeratosis with pseudoainhum, ichthyosis, erythrokeratoderma and collodion babies that later develop into ichthyosiform erythrodema. Mutant loricrin accumulates in the nucleus and interferes in the mitosis and apoptosis processes in the keratinocytes. The treatment of the disease consists in administration of keratolytics and retinoids and surgical removal of the pseudoainhum. In the present study, sequencing of both exons of the loricrin gene was conducted in individuals of a family of Minas Gerais. The family members are two girls, sisters, clinically suspected as having the disease, and their parents, both healthy. The passed paternal grandfather of the girls had similar symptoms. The sequencing showed two insertions and three punctual alterations at the second exon in affected individuals. These alterations cant be considered causative of the symptoms presented. New approaches and other possible related genes must be investigated to establish the causes of the aberrant phenotypes.